Analisis Faktor Yang Mempengaruhi Penyerapan Anggaran Badan Layanan Umum Daerah Pada Puskesmas Di Kabupaten Klaten - Heni Sulistyowati; Yuwita Ariessa Pravasanti; Indra Lila Kusuma (Jurnal Akuntansi dan Pajak, 2022)
This study aims to determine the effect of budget planning, budget execution, public accountability & human resource competence on the absorption of the budget of the regional public service agency at the Puskesmas in Klaten Regency. The research method used is quantitative research. Sources of data used are primary data obtained from distributing questionnaires. The population in this study was the financial department of the Puskesmas and the Head of the Puskesmas in 29 Klaten District Health Centers with a total of 58 respondents. The sampling technique used a saturated sample. The data in this study were processed using multiple linear regression with the help of the SPSS version 24 program. Based on the results of the study, it can be concluded that budget planning and budget execution have a positive influence on the absorption of the budget of regional public service agencies at the Puskesmas in Klaten Regency, while Public Accountability and Competence of human resources does not affect the absorption of the budget of local public service agencies at the Puskesmas in Klaten Regency. Keywords: Budget Planning, Budget Execution, Public Accountability, Human Resource Competence, and Budget Absorption.